A gadolinium-based contrast agent composite material with high relaxivity and its preparation method and application

By inlaid and assembling calcium phosphate in a single molecule micelle and carrying a gadolinium-based contrast agent, the problem of difficulty in balancing relaxation rate and biosafety in the prior art is solved, and the effects of high relaxation rate, rapid degradation and excellent biocompatibility are achieved.

CN119113154BActive Publication Date: 2025-03-25SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI

Patent Information

Application Number
CN202411612554.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

While increasing the relaxation rate, the existing gadolinium-based T1 contrast agents are difficult to balance high thermodynamic stability, water solubility and biodegradability, which poses safety risks.

Method used

By assembling calcium phosphate between adjacent blocks of a single molecule micelle and carrying the gadolinium-based contrast agent in calcium phosphate, the rotation correlation time of the gadolinium-based contrast agent is significantly prolonged, its relaxation rate is improved, and rapid biodegradable performance is achieved in an acidic environment.

Benefits of technology

It significantly improves the relaxation rate of gadolinium-based contrast agent, enhances the sensitivity of MRI diagnosis, and achieves rapid reduction in interpretation and release in a short period of time, extends the window time of imaging, and has excellent biocompatibility and low toxicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113154B_ABST
    Figure CN119113154B_ABST
Patent Text Reader

Abstract

The present invention provides a gadolinium-based contrast agent composite material with high relaxivity, and a preparation method and application thereof, wherein the gadolinium-based contrast agent composite material comprises a gadolinium-based contrast agent, calcium phosphate and a single-molecule micelle; calcium phosphate is embedded and assembled between adjacent blocks of the single-molecule micelle; and the gadolinium-based contrast agent is encapsulated in calcium phosphate. The present invention can significantly prolong the rotation correlation time of the gadolinium-based contrast agent by embedding and assembling calcium phosphate between adjacent blocks of the single-molecule micelle and encapsulating and fixing the gadolinium-based contrast agent in calcium phosphate, thereby effectively increasing its relaxivity. At the same time, the gadolinium-based contrast agent composite material has excellent biodegradability in an acidic environment, and can achieve rapid response degradation and release in a short time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of MRI diagnostic contrast agents, and relates to a gadolinium-based contrast agent composite material with high relaxivity, and a preparation method and application thereof. Background Art

[0002] Magnetic resonance imaging (MRI) is a non-invasive tomography technology, which is well-known for its excellent spatial resolution, superior soft tissue contrast, non-ionizing radiation and lack of tissue penetration depth limitation. It has been widely used in clinical tumor diagnosis. The combination of contrast agents and MRI can significantly enhance the distinction between normal tissue and pathological areas, further expanding the clinical application scope of MRI technology.

[0003] T1 contrast agents can provide contrast brightening signals by shortening the longitudinal relaxation time of surrounding water protons, which is beneficial for distinguishing lesions and studying tissue morphology, and can effectively improve the accuracy of early tumor diagnosis. Currently, most of the T1 contrast agents used in clinical practice are small molecule GBCAs. However, a large amount of clinical data shows that commercially available GBCAs have a series of safety risks. Therefore, how to improve the performance of gadolinium-based T1 contrast agents to reduce the dose required for diagnosis is a potential solution to its safety problem.

[0004] The most direct and effective way to improve the performance of GBCAs is to increase their relaxivity. Compared with the theoretical value, the relaxivity of commercially available GBCAs still has a lot of room for improvement. Gadolinium-based contrast agents with higher relaxivity can allow for lower dose administration, thereby reducing the risk of gadolinium ion-induced toxicity. In recent years, methods that can be used to improve the relaxivity of GBCAs include: increasing the q value by reducing the number of teeth of the chelating agent, extending τR by increasing the molecular weight of GBCAs, and optimizing τm by weakening the coordination bond energy of coordinated water.

[0005] However, it is difficult to balance the high relaxivity, high thermodynamic stability, good water solubility and excellent biodegradability of an ideal contrast agent. Therefore, it is an urgent problem for those skilled in the art to design a gadolinium-based T1 contrast agent that has the above properties and is more in line with the safety requirements of clinical use. Summary of the invention

[0006] The purpose of the present invention is to provide a gadolinium-based contrast agent composite material with high relaxivity, and a preparation method and application thereof. By embedding and assembling calcium phosphate between adjacent blocks of single-molecule micelles and encapsulating the gadolinium-based contrast agent in the calcium phosphate, the rotation correlation time of the gadolinium-based contrast agent can be significantly prolonged, thereby effectively increasing its relaxivity. At the same time, the gadolinium-based contrast agent composite material has excellent biodegradability in an acidic environment, and can achieve rapid response degradation and release in a short time.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a gadolinium-based contrast agent composite material with high relaxivity, the gadolinium-based contrast agent composite material comprising a gadolinium-based contrast agent, calcium phosphate and a single-molecule micelle;

[0009] Calcium phosphate is embedded and assembled between adjacent blocks of the unimolecular micelle;

[0010] The gadolinium-based contrast agent is entrapped in calcium phosphate.

[0011] In the present invention, the gadolinium-based contrast agent composite material is a T1-type contrast agent; and the single-molecule micelle can be uniformly dispersed in water.

[0012] The gadolinium-based contrast agent composite material provided by the present invention can significantly prolong the rotation correlation time of the gadolinium-based contrast agent, thereby effectively increasing its relaxation rate, by embedding and assembling calcium phosphate between adjacent blocks of single-molecule micelles and encapsulating the gadolinium-based contrast agent in the calcium phosphate. In addition, calcium phosphate has excellent biodegradability in an acidic environment and can be rapidly degraded and released in a short time. Therefore, the gadolinium-based contrast agent composite material can have excellent safety performance while ensuring high relaxation performance.

[0013] It is worth noting that, using single-molecule micelles as templates and utilizing the abundant active sites inside the single-molecule micelles, free phosphate groups and calcium ions are assembled by precipitation in the single-molecule micelles to form calcium phosphate with a hydroxyapatite structure. Moreover, due to the monodispersity of the single-molecule micelles themselves, the formation of calcium phosphate with uniform size can be guided and controlled. At the same time, since the gadolinium-based contrast agent molecules are also rich in carboxyl groups, they can be incorporated into the calcium phosphate through interaction with calcium ions during the calcium phosphate assembly process. The gadolinium-based contrast agent can be fixed in the calcium phosphate through physical encapsulation, thereby prolonging the rotation correlation time of the gadolinium-based contrast agent and improving the sensitivity of MRI diagnosis.

[0014] As a preferred technical solution of the present invention, the gadolinium-based contrast agent includes any one of Gd-DO3A, Gd-DOTA or Gd-DTPA.

[0015] In the present invention, Gd-DO3A, Gd-DOTA and Gd-DTPA are all commercially available products.

[0016] As a preferred technical solution of the present invention, the unimolecular micelle comprises a cyclodextrin-based star-shaped block copolymer.

[0017] Preferably, the average particle size of the cyclodextrin-based star-shaped block copolymer is 30-50 nm, for example, 32 nm, 35 nm, 36 nm, 38 nm, 40 nm, 42 nm, 45 nm, 46 nm or 48 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] Preferably, the molecular formula of the cyclodextrin-based star-shaped block copolymer is β-CD-g-[An-b-Bm] 21 , wherein A is the first hydrophilic block, n is the degree of polymerization of the first hydrophilic block, B is the second hydrophilic block, and m is the polymer of the second hydrophilic block.

[0019] Preferably, the first hydrophilic block comprises polyacrylic acid (PAA).

[0020] Preferably, the value of n is 50-60, for example, it can be 51, 52, 53, 54, 55, 56, 57, 58 or 59, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the second hydrophilic block comprises poly(polyethylene glycol methyl ether acrylate) or poly(polyethylene glycol methyl ether methacrylate).

[0022] Preferably, the value of m is 8-20, for example, it can be 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 or 19, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] It is worth noting that the degree of polymerization of the first hydrophilic block and the second hydrophilic block needs to be strictly controlled to obtain suitable single-molecule micelles, thereby effectively increasing the longitudinal relaxation rate of the gadolinium-based contrast agent.

[0024] It is worth noting that the blocks in the cyclodextrin-based star-shaped block copolymer are rich in carboxyl groups, so the free phosphate groups and calcium ions can be assembled by block precipitation in the single-molecule micelles to form calcium phosphate. The monodispersity of the single-molecule micelles and the hydrophilic polymer of the second hydrophilic block can limit the further growth of calcium phosphate, guide and control the formation of calcium phosphate with uniform size, and give the material good water solubility.

[0025] As a preferred technical solution of the present invention, the method for preparing the cyclodextrin-based star-shaped block copolymer comprises the following steps:

[0026] (1) mixing a first polymerizable monomer, an initiator, a catalytic composition and a first solvent, and performing a first free radical polymerization reaction to obtain a first polymer precursor;

[0027] (2) mixing a second polymerizable monomer, a catalytic composition, a second solvent, and the first polymer precursor obtained in step (1), and performing a second free radical polymerization reaction to obtain a cyclodextrin-based star-shaped block copolymer precursor;

[0028] (3) subjecting the cyclodextrin-based star-shaped block copolymer precursor obtained in step (2) to a hydrolysis reaction to obtain the cyclodextrin-based star-shaped block copolymer.

[0029] In the present invention, 21-Br-β-CD is used as an initiator, and the first polymerization monomer and the second polymerization monomer are polymerized in sequence by segmented ATRP polymerization, and then subjected to a hydrolysis reaction to obtain the cyclodextrin-based star-shaped block copolymer.

[0030] As a preferred technical solution of the present invention, the catalytic composition includes a catalyst and a catalyst ligand.

[0031] Preferably, the catalyst comprises cuprous bromide or cuprous chloride; and the catalyst ligand comprises pentamethyldiethylenetriamine (PMDETA).

[0032] Preferably, in step (1), the first polymerizable monomer comprises tert-butyl acrylate (tBA).

[0033] Preferably, the initiator in step (1) comprises 21-Br-β-CD.

[0034] In the present invention, the 21-Br-β-CD is a fully brominated macromolecular initiator obtained by reacting β-cyclodextrin as a starting material with 2-bromoisobutyryl bromide (BIBB). The preparation method thereof is not specifically limited, and those skilled in the art can prepare it according to the method provided by the prior art.

[0035] Preferably, in step (1), the first solvent comprises methyl ethyl ketone.

[0036] Preferably, the molar ratio of the initiator to the first polymerization monomer in step (1) is 1:(500-600), for example, 1:510, 1:520, 1:530, 1:540, 1:550, 1:560, 1:570, 1:580 or 1:590, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, the temperature of the first free radical polymerization reaction in step (1) is 50-70°C, for example, 52°C, 55°C, 56°C, 58°C, 60°C, 62°C, 65°C, 66°C or 68°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] Preferably, the time of the first free radical polymerization reaction in step (1) is 5-8 h, for example, 5.5 h, 6 h, 6.5 h, 7 h or 7.5 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] In the present invention, the specific method of the first free radical polymerization reaction in step (1) comprises: dissolving an initiator in a first solvent, then adding a first polymerization monomer and a catalyst ligand thereto, removing excess oxygen in the reaction system, then adding a catalyst under an argon atmosphere, and carrying out the first free radical polymerization reaction for 5-8 hours at a temperature of 50-70°C with stirring.

[0040] Preferably, in step (2), the second polymerizable monomer comprises polyethylene glycol methyl ether acrylate (OEG) or polyethylene glycol methyl ether methacrylate (MPEG-MMA).

[0041] Preferably, in step (2), the second solvent comprises dioxane.

[0042] Preferably, in step (2), the molar ratio of the second polymerizable monomer to the first polymer precursor is 1:(90-110), for example, it can be 1:92, 1:95, 1:96, 1:98, 1:100, 1:102, 1:105, 1:106 or 1:108, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0043] Preferably, the temperature of the second free radical polymerization reaction in step (2) is 50-70°C, for example, 52°C, 55°C, 56°C, 58°C, 60°C, 62°C, 65°C, 66°C or 68°C, but is not limited to the listed values, and other values ​​within the numerical range not listed are also applicable.

[0044] Preferably, the time of the second free radical polymerization reaction in step (2) is 22-30 h, for example, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h or 29 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0045] In the present invention, the specific method of the second free radical polymerization reaction in step (2) comprises: dissolving the first polymer precursor, the second polymerization monomer and the catalyst ligand in a second solvent, removing excess oxygen in the reaction system, and then adding a catalyst under an argon atmosphere, and conducting the second free radical polymerization reaction at a temperature of 50-70° C. for 22-30 hours with stirring.

[0046] In the present invention, the post-treatment steps of the first free radical polymerization reaction and the second free radical polymerization reaction are not limited, and the specific post-treatment method can be carried out according to the method provided by the prior art.

[0047] Preferably, the temperature of the hydrolysis reaction in step (3) is 20-30°C, for example, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C or 29°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0048] Preferably, the hydrolysis reaction time in step (3) is 22-30 h, for example, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h or 29 h, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0049] In the present invention, the specific method of the hydrolysis reaction in step (3) comprises: dissolving the cyclodextrin-based star-shaped block copolymer precursor in dichloromethane, then adding trifluoroacetic acid (TFA), and then performing a hydrolysis reaction at a temperature of 20-30° C. for 22-30 hours.

[0050] In the present invention, after the hydrolysis reaction in step (3), suction filtration, dichloromethane washing and vacuum drying are performed.

[0051] As a preferred technical solution of the present invention, the mass ratio of the gadolinium-based contrast agent to the unimolecular micelle is 1:(7-12), for example, it can be 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10, 1:10.5, 1:11 or 1:11.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0052] Preferably, the average particle size of the gadolinium-based contrast agent composite material is 20-40 nm, for example, it can be 22 nm, 25 nm, 26 nm, 28 nm, 30 nm, 32 nm, 35 nm, 36 nm or 38 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0053] Preferably, the longitudinal relaxation rate of the gadolinium-based contrast agent composite material is greater than 80 mM -1 s -1 , for example, it can be 82mM -1 s -1 、85mM -1 s -1 、87mM -1 s -1 、90mM -1 s -1 、92mM -1 s -1 or 95mM -1 s -1The above values ​​are not limited to the above values, and other values ​​not listed in the above values ​​are also applicable.

[0054] It is worth noting that the longitudinal relaxation rate of the gadolinium-based contrast agent composite material is greater than 80 mM -1 s -1 , while the longitudinal relaxation rate of commercial Gd-DTPA small molecule is only 4.36mM -1 s -1 The longitudinal relaxivity value of the contrast agent of the present invention is nearly 20 times that of the commercial contrast agent, indicating that the gadolinium-based contrast agent composite material of the present invention has a very high sensitivity, that is, a smaller amount can achieve a better effect; in addition, the in vitro release experiment also shows that the gadolinium-based contrast agent composite material begins to decompose in 5 minutes under acidic conditions and can be basically decomposed in 12 hours, and it has good safety performance. The above two advantages effectively make up for the defects of commercial contrast agents and pave the way for future commercialization.

[0055] In a second aspect, the present invention provides a method for preparing the gadolinium-based contrast agent composite material as described in the first aspect, the preparation method comprising:

[0056] Mixing the single-molecule micelle, the first salt solution and the second salt solution, and performing a hydrothermal reaction to obtain the gadolinium-based contrast agent composite material;

[0057] The first saline solution comprises the following components: a gadolinium-based contrast agent, a phosphate salt, a sodium salt, and a first buffer;

[0058] The second salt solution includes the following components: a calcium salt and a second buffer.

[0059] The preparation method provided by the present invention can form calcium phosphate by precipitation and assembly of free phosphate radicals and calcium ions in carboxyl-rich single-molecule micelles through a one-step hydrothermal synthesis method, and the gadolinium-based contrast agent small molecules are fixed in the obtained calcium phosphate. The preparation method is simple and convenient, and has low cost.

[0060] As a preferred technical solution of the present invention, the mixing method includes: mixing the unimolecular micelles and the first salt solution, and then adding the second salt solution thereto.

[0061] In the present invention, the mixing is performed under vortexing.

[0062] Preferably, the unimolecular micelle comprises a cyclodextrin-based star-shaped block copolymer.

[0063] Preferably, the phosphate includes any one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium phosphate, potassium dihydrogen phosphate or dipotassium hydrogen phosphate, or a combination of at least two thereof.

[0064] Preferably, the sodium salt comprises sodium chloride.

[0065] Preferably, the first buffer comprises HEPES saline solution.

[0066] Preferably, the molar ratio of the gadolinium-based contrast agent, phosphate and sodium salt is 1:(2-4):(60-80), for example, it can be 1:2:60, 1:2.5:60, 1:3:70, 1:3.5:70, 1:3:80 or 1:4:80, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0067] Preferably, the mass volume ratio of the gadolinium-based contrast agent and the first buffer is 1 mg:(0.8-2) mL, for example, it can be 1 mg:1 mL, 1 mg:1.2 mL, 1 mg:1.5 mL, 1 mg:1.6 mL or 1 mg:1.8 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Preferably, the calcium salt includes any one of calcium chloride, calcium nitrate or calcium acetate, or a combination of at least two of them.

[0069] Preferably, the second buffer comprises Tris-HCl solution.

[0070] Preferably, the molar ratio of the gadolinium-based contrast agent to the calcium salt is 1:(120-130), for example, it can be 1:121, 1:122, 1:123, 1:124, 1:125, 1:126, 1:127, 1:128 or 1:129, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] Preferably, the mass volume ratio of the calcium salt and the second buffer is (25-30) mg:1 mL, for example, it can be 26 mg:1 mL, 27 mg:1 mL, 28 mg:1 mL or 29 mg:1 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] Preferably, the temperature of the hydrothermal reaction is 110-130°C, for example, it can be 112°C, 115°C, 116°C, 118°C, 120°C, 122°C, 125°C, 126°C or 128°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] Preferably, the hydrothermal reaction time is 20-30 min, for example, it can be 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min or 29 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] Preferably, the hydrothermal reaction is followed by dialysis and freeze-drying.

[0075] In a third aspect, the present invention provides a contrast composition, comprising a pharmaceutically acceptable adjuvant and the gadolinium-based contrast agent composite material described in the first aspect;

[0076] The adjuvant includes a diluent.

[0077] The present invention also provides a non-medical imaging method, which comprises: administering the gadolinium-based contrast agent composite material described in the first aspect or the imaging composition described in the third aspect to a subject to be imaged, and performing imaging.

[0078] In a fourth aspect, the present invention provides a use of the gadolinium-based contrast agent composite material as described in the first aspect, wherein the gadolinium-based contrast agent composite material is used for the preparation of tumor magnetic resonance imaging or detection reagents.

[0079] Compared with the prior art, the present invention has the following beneficial effects:

[0080] (1) The gadolinium-based contrast agent composite material provided by the present invention can significantly prolong the rotation correlation time of the gadolinium-based contrast agent by assembling calcium phosphate of uniform size between adjacent blocks of single-molecule micelles and fixing the gadolinium-based contrast agent in calcium phosphate by physical encapsulation, thereby effectively increasing its relaxation rate and improving the sensitivity of MRI diagnosis;

[0081] (2) The gadolinium-based contrast agent composite material provided by the present invention has excellent biodegradability and safety performance in an acidic environment, can achieve rapid response degradation and release in a short time, and prolong the imaging window time;

[0082] (3) The preparation method provided by the present invention can form calcium phosphate by precipitation and assembly of free phosphate and calcium ions in the embedded segment of carboxyl-rich single-molecule micelles through a one-step hydrothermal synthesis method, and the gadolinium-based contrast agent is fixed in the obtained calcium phosphate; the preparation method is simple, convenient and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0083] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of 21-Br-β-CD provided in the present invention;

[0084] Figure 2β-CD-g-[PtBA(50)] prepared in Example 1 21 H NMR spectrum;

[0085] Figure 3 β-CD-g-[PtBA(50)-b-POEG(10)] prepared in Example 1 21 H NMR spectrum;

[0086] Figure 4 β-CD-g-[PAA(50)-b-POEG(10)] prepared in Example 1 21 H NMR spectrum;

[0087] Figure 5 β-CD-g-[PAA(50)-b-POEG(10)] prepared in Example 1 21 TEM images of

[0088] Figure 6 is a TEM image of the gadolinium-based contrast agent composite material prepared in Example 1;

[0089] Figure 7 This is a comparison diagram of the longitudinal relaxation rate (r1) and the transverse relaxation rate (r2) of the gadolinium-based contrast agent composite material prepared in Example 1;

[0090] Figure 8 A comparison chart of the longitudinal relaxation rate (r1) and the transverse relaxation rate (r2) of the gadolinium-based contrast agent provided in Comparative Example 1;

[0091] Fig. 9 This is a diagram of tissue toxicity test of the gadolinium-based contrast agent composite material prepared in Example 1 on BALB / c mice;

[0092] Fig.10 This is a graph showing the cytotoxicity test of the gadolinium-based contrast agent composite material prepared in Example 1 in mouse breast cancer cells;

[0093] Fig.11 This is a graph showing the cytotoxicity test of the gadolinium-based contrast agent composite material prepared in Example 1 in human umbilical vein endothelial cells;

[0094] Fig.12 These are in vivo T1-weighted MRI images of the contrast agent materials in Example 1 and Comparative Example 1 in tumor-bearing mice transplanted with 4T1 cells. DETAILED DESCRIPTION

[0095] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0096] Unless otherwise specified, the raw materials and reagents used in the following examples and comparative examples are commercially available products or can be prepared by known methods. Specific technical or condition parameters are not specified in the following examples and comparative examples, and can be carried out according to the technology or conditions described in the literature in the field or according to the product instructions.

[0097] The initiator (21-Br-β-CD) in the following examples was prepared by the following preparation method, which specifically includes: placing β-CD (6.82 g, 6 mmol, vacuum dried for 12 h using phosphorus pentoxide at 80 ° C) in a 200 mL flask, then adding 60 mL of anhydrous N-methylpyrrolidone, placing it in an ice-water bath, cooling it to 0 ° C, slowly adding 2-bromoisobutyryl bromide (58.0 mL, 252 mmol) under magnetic stirring, reacting for 2 h in an ice bath, raising the system temperature to room temperature, continuing to react for 22 h, and then vacuum drying to obtain a syrupy product, adding 100 mL of dichloromethane to the flask for dilution, and then washing it several times with a saturated NaHCO3 aqueous solution and deionized water in turn. The obtained organic layer was vacuum dried, and finally crystallized in n-hexane below -20 ° C, and the obtained white precipitate was 21-Br-β-CD. The nuclear magnetic resonance hydrogen spectrum of 21-Br-β-CD is shown as follows Figure 1 As shown, it confirmed the correct synthesis of 21-Br-β-CD.

[0098] Example 1

[0099] This embodiment provides a gadolinium-based contrast agent composite material with high relaxivity and a preparation method thereof, wherein the gadolinium-based contrast agent composite material comprises a gadolinium-based contrast agent, calcium phosphate and a single-molecule micelle;

[0100] Calcium phosphate is embedded and assembled between adjacent blocks of the single-molecule micelle; the gadolinium-based contrast agent is encapsulated in the calcium phosphate;

[0101] The gadolinium-based contrast agent is Gd-DTPA;

[0102] The unimolecular micelle is a cyclodextrin-based star-shaped block copolymer with an average particle size of 35 nm; the molecular formula of the cyclodextrin-based star-shaped block copolymer is β-CD-g-[PAA(50)-b-POEG(10)] 21 ;

[0103] The mass ratio of the gadolinium-based contrast agent to the single-molecule micelle is 1:8.77; the average particle size of the gadolinium-based contrast agent composite material is 30 nm;

[0104] The method for preparing the cyclodextrin-based star-shaped block copolymer comprises the following steps:

[0105] (1) 21-Br-β-CD (84.92 mg, 0.02 mmol) was placed in a 200 mL Schlenk flask, and then 37 mL of methyl ethyl ketone, tBA (36.9 mL, 252 mmol) and PMDETA (175 μL, 0.84 mmol) were added thereto in sequence. The reaction system was then frozen and deoxygenated three times. Cuprous bromide (60.25 mg, 0.42 mmol) was added thereto under an argon atmosphere. The first free radical polymerization reaction was then carried out under stirring at 60 °C for 7 h. The Schlenk flask was then placed in liquid nitrogen to quickly terminate the reaction. Acetone was then added to dilute the mixture, and the mixture was passed through a neutral alumina column. The effluent was collected and precipitated three times with a mixed solvent of methanol and water in a volume ratio of 1:1. The precipitate was collected and dried in vacuo to obtain the first polymer precursor β-CD-g-[PtBA(50)]. 21 ;

[0106] (2) OEG (3.36 g, 7 mmol), PMDETA (29 μL, 0.14 mmol) and β-CD-g-PtBA(50) (0.5 g, 0.0033 mmol) prepared in step (1) were placed in a 20 mL Schlenk bottle, and then 5 mL of anhydrous dioxane was added to completely dissolve the mixture. The reaction system was then frozen and deoxygenated three times. Cuprous bromide (10 mg, 0.07 mmol) was added under an argon atmosphere, and then a second free radical polymerization reaction was carried out at 60°C with stirring for 24 h. After the reaction, the mixture was dialyzed using a dialysis bag with a molecular weight cutoff of 14,000 Da (the dialysate on the first day was prepared using 12.5 g EDTA-2Na and 1.34 g NaOH dissolved in 3 L deionized water; the dialysates thereafter were all deionized water). After freeze-drying, a cyclodextrin-based star block copolymer precursor β-CD-g-[PtBA(50)-b-POEG(10)] was obtained. 21 ;

[0107] (3) Add 0.5 g of β-CD-g-[PtBA(50)-b-POEG(10)] 21 The product was dissolved in 30 mL of dichloromethane, and then 10 mL of TFA was added thereto, and then the hydrolysis reaction was carried out under stirring at 25 °C for 24 h. The hydrolysis product β-CD-g-[PAA(50)-b-POEG(10)] 21 The precipitate was filtered off and washed with dichloromethane for three times, and finally vacuum dried at 40° C. for 24 hours to obtain the cyclodextrin-based star-shaped block copolymer.

[0108] The preparation method of the gadolinium-based contrast agent composite material comprises: mixing 50 mg of β-CD-g-[PAA(50)-b-POEG(10)] 21Dissolved in 5 mL of the first salt solution, then added with 5 mL of the second salt solution under vortexing, and then continued to vortex for 1 min, followed by hydrothermal reaction at a temperature of 120° C. for 20 min, dialyzed using a dialysis bag with a molecular weight cutoff of 3500 Da, and then freeze-dried to obtain the gadolinium-based contrast agent composite material;

[0109] The first salt solution is a mixed solution of 2mM Gd-DTPA (5.7mg), 6mM Na2HPO4, 140mM NaCl and HEPES salt solution (5mL, 50mM, pH=7.1); the second salt solution is a mixed solution of 250mM CaCl2 and Tris-HCl solution (5mL, 10mM, pH=7.6).

[0110] In this embodiment, the β-CD-g-[PtBA(50)] obtained in step (1) 21 The H NMR spectrum of Figure 2 As shown, it supports the conclusion that β-CD-g-[PtBA(50)] 21 The correct synthesis of step (2) β-CD-g-[PtBA(50)-b-POEG(10)] 21 The H NMR spectrum of Figure 3 As shown, it supports the conclusion that β-CD-g-[PtBA(50)-b-POEG(10)] 21 The nuclear magnetic resonance hydrogen spectrum and TEM image of the cyclodextrin-based star-shaped block copolymer obtained in step (3) are shown as follows: Figure 4 and Figure 5 As shown, it supports the conclusion that β-CD-g-[PAA(50)-b-POEG(10)] 21 The correct synthesis.

[0111] In this embodiment, the TEM image of the obtained gadolinium-based contrast agent composite material is as follows: Figure 6 As shown by Figure 6 It can be seen that the particle size distribution of the gadolinium-based contrast agent composite material is uniform.

[0112] The gadolinium-based contrast agent composite material obtained in this embodiment can significantly prolong the rotation correlation time of the gadolinium-based contrast agent by embedding and assembling calcium phosphate between adjacent blocks of single-molecule micelles and encapsulating the gadolinium-based contrast agent in calcium phosphate, so that its longitudinal relaxation rate is much higher than that of the commercially available Gd-DTPA contrast agent, thereby improving the sensitivity of MRI diagnosis.

[0113] Example 2

[0114] This embodiment provides a gadolinium-based contrast agent composite material and a preparation method thereof, except that the molecular formula of the cyclodextrin-based star-shaped block copolymer is β-CD-g-[PAA(60)-b-POEG(10)] 21 , and adjusting the preparation method parameters of the cyclodextrin-based star-shaped block copolymer accordingly, other conditions are the same as those in Example 1.

[0115] The gadolinium-based contrast agent composite material obtained in this embodiment can significantly prolong the rotation correlation time of the gadolinium-based contrast agent by embedding and assembling calcium phosphate between adjacent blocks of single-molecule micelles and encapsulating the gadolinium-based contrast agent in calcium phosphate, so that its longitudinal relaxation rate is much higher than that of the commercially available Gd-DTPA contrast agent, thereby improving the sensitivity of MRI diagnosis.

[0116] Example 3

[0117] This embodiment provides a gadolinium-based contrast agent composite material and a preparation method thereof, except that the molecular formula of the cyclodextrin-based star-shaped block copolymer is β-CD-g-[PAA(50)-b-POEG(20)] 21 , and adjusting the preparation method parameters of the cyclodextrin-based star-shaped block copolymer accordingly, other conditions are the same as those in Example 1.

[0118] The gadolinium-based contrast agent composite material obtained in this embodiment can significantly prolong the rotation correlation time of the gadolinium-based contrast agent by embedding and assembling calcium phosphate between adjacent blocks of single-molecule micelles and encapsulating the gadolinium-based contrast agent in calcium phosphate, so that its longitudinal relaxation rate is much higher than that of the commercially available Gd-DTPA contrast agent, thereby improving the sensitivity of MRI diagnosis.

[0119] Example 4

[0120] This embodiment provides a gadolinium-based contrast agent composite material and a preparation method thereof, except that the molecular formula of the cyclodextrin-based star-shaped block copolymer is β-CD-g-[PAA(97)-b-POEG(10)] 21 , and adjusting the preparation method parameters of the cyclodextrin-based star-shaped block copolymer accordingly, other conditions are the same as those in Example 1.

[0121] The gadolinium-based contrast agent composite material obtained in this example has a high degree of polymerization of its first hydrophilic block, so the calcium phosphate particles formed are relatively large, and the surrounding POEG is insufficient to provide good water dispersibility, and cannot be used as an excellent contrast agent.

[0122] Example 5

[0123] This embodiment provides a gadolinium-based contrast agent composite material and a preparation method thereof, except that the molecular formula of the cyclodextrin-based star-shaped block copolymer is β-CD-g-[PAA(97)-b-POEG(5)]21 , and adjusting the preparation method parameters of the cyclodextrin-based star-shaped block copolymer accordingly, other conditions are the same as those in Example 1.

[0124] The gadolinium-based contrast agent composite material obtained in this embodiment cannot effectively restrict the growth of calcium phosphate due to its low degree of polymerization of the second hydrophilic block, thereby failing to form calcium phosphate with regular morphology and limiting the rotation and flipping of Gd-DTPA, thereby failing to obtain a contrast agent with high relaxivity.

[0125] Comparative Example 1

[0126] This comparative example provides a gadolinium-based contrast agent, wherein the gadolinium-based contrast agent is Gd-DTPA.

[0127] The gadolinium-based contrast agent provided in this comparative example has a small molecular weight and can be metabolized quickly by the kidneys. It has a very short imaging window and a low longitudinal relaxation rate, which results in low sensitivity of MRI diagnosis. In addition, the required dosage is large, which is not conducive to biosafety.

[0128] Responsiveness testing

[0129] The longitudinal relaxation time and transverse relaxation time of the MRI contrast agents obtained in Example 1 of the present invention and Comparative Example 1 were tested on a 0.5T MRI tester. The specific testing method includes: preparing the above samples with iron concentrations of 0.0039 mM, 0.0078 mM, 0.0156 mM, 0.0313 mM, and 0.0625 mM, respectively, and after testing on a 0.5T MRI tester, linear fitting was performed with gadolinium ion concentration (mM) as the abscissa and the reciprocal of the longitudinal relaxation time and the transverse relaxation time as the ordinate to obtain the longitudinal relaxation rate (r1) and transverse relaxation rate (r2) of the MRI contrast agents in Example 1 and Comparative Example 1; wherein the units of r1 and r2 are both mM -1 s -1 ; r2 / r1 is the gold standard for evaluating the type of contrast agent. Usually, if the r2 / r1 ratio is less than 5, it can be considered a typical T1 contrast agent. The smaller the r2 / r1 ratio, the better the T1 contrast performance; if the r2 / r1 ratio is greater than 8, it can be considered a typical T2 contrast agent.

[0130] The fitting results of the MRI contrast agents in Example 1 and Comparative Example 1 are as follows: Figure 7 and Figure 8 shown.

[0131] Depend on Figure 7 It can be seen that the r1 and r2 of the gadolinium-based contrast agent composite material obtained in Example 1 are 84.96 mM -1 s -1 and 101.34 mM -1 s-1 , the ratio of r2 / r1 is 1.193. Figure 8 It can be seen that the r1 and r2 of the gadolinium-based contrast agent obtained in Comparative Example 1 are 4.36 mM -1 s -1 and 5.22 mM -1 s -1 , the ratio of r2 / r1 is 1.197. From the comparison between the two, it can be seen that the longitudinal relaxation rate r1 of the gadolinium-based contrast agent composite material obtained in Example 1 can reach 84.96 mM -1 s -1 , while the longitudinal relaxation rate r1 of the commercially available Gd-DTPA small molecule in Comparative Example 1 is only 4.36 mM -1 s -1 The longitudinal relaxation rate value of the MRI contrast agent obtained in Example 1 is nearly 20 times that of the commercial contrast agent, which shows that the gadolinium-based contrast agent composite material has a very high sensitivity and a better effect can be achieved by using a smaller amount.

[0132] Biological tissue toxicity performance test

[0133] The gadolinium-based contrast agent composite material obtained in Example 1 of the present invention is subjected to a biological tissue toxicity test, and the operation method includes:

[0134] H&E staining was used to evaluate the tissue toxicity of contrast agents in normal BALB / c mice (4-6 weeks old, 20 g). BALB / c mice were divided into two groups, an experimental group and a control group. In the experimental group, the first group of mice was injected with 150 μL of a saline solution containing the gadolinium-based contrast agent composite material obtained in Example 1 through the tail vein, wherein the concentration of gadolinium ions in the solution was 0.1 mM / kg. The control group received an injection of the same volume of a saline solution containing the gadolinium-based contrast agent obtained in Comparative Example 1, wherein the concentration of gadolinium ions in the solution was 0.1 mM / kg. After being raised under normal conditions for 3 days, the mice were killed by cervical dislocation, and the heart, liver, spleen, lungs and kidneys were collected, and H&E stained sections were prepared, and observed and photographed using a microscope.

[0135] The results are as follows Fig. 9 As shown, there were no significant differences in cell morphology and tissue structure between the experimental group and the control group. In the liver sections, the morphology and structure of the hepatocytes were normal, and no inflammatory reaction was observed; no signs of renal fibrosis were found in the kidney sections. This shows that the gadolinium-based contrast agent composite material of the present invention does not cause obvious toxic reactions in vivo, has good biosafety, and demonstrates its potential for wide application in the biomedical field.

[0136] Cytotoxicity performance test

[0137] The gadolinium-based contrast agent composite material obtained in Example 1 of the present invention was subjected to toxicity tests on normal cells and cancer cells. The CCK-8 method was used to determine the cytotoxicity of the contrast agent in mouse breast cancer cells (4T1) and human umbilical vein endothelial cells (HUVEC).

[0138] Taking 4T1 cells as an example, the test method includes: 100 μL of 4T1 cells are seeded in a 96-well plate at a density of 5000 cells per well, the 96-well plate is placed in a CO2 incubator, and cultured at 37°C for 24 hours, then the contrast agent is dissolved in a complete culture medium, and gradiently diluted to multiple concentrations (9 different concentrations of 0.008-2.00 mM were used in this test example), added to the wells of the 96-well plate, and incubated with the cells for 24 hours, and then 100 μL of 10% CCK-8 solution was added to each well, and then placed in a cell culture incubator for incubation for 3 hours, and then the absorbance value (OD) at a wavelength of 450 nm was measured by an ELISA instrument. 450nm ). Make 4 parallel samples for each contrast agent concentration (called experimental group) and control group. Calculate the relative survival rate of cells based on the absorbance value. The blank group is the complete culture medium without cells, and the control group is the cell culture medium without contrast agent.

[0139] The cytotoxicity test of HUVEC cells was basically the same as that of 4T1 cells described above.

[0140] Relative cell survival rate (%) = 100 × (OD of experimental group - OD of blank group) / (OD of control group - OD of blank group)

[0141] like Fig.10 and Fig.11 As shown, 4T1 and HUVEC cells showed high activity levels at all tested concentrations. Even at a gadolinium concentration of 2 mM, the survival rates of 4T1 cells and HUVEC cells were above 98%. This shows that the gadolinium-based contrast agent composite material of the present invention has minimal cytotoxicity and good biocompatibility.

[0142] MRI imaging experimental test

[0143] The contrast agents obtained in Example 1 and Comparative Example 1 of the present invention were subjected to an in vivo MRI imaging experiment, and the operation method thereof includes:

[0144] A batch of BALB / c mice (4-6 weeks old, weighing 20 g) that met SPF conditions were purchased, and 4T1 cells were selected as subcutaneous tumor model cells. First, 4T1 cells were cultured and evenly dispersed in PBS solution at a density of 2×10 6cells / mL, and then 100 μL of PBS solution was injected subcutaneously in the axilla of each BALB / c mouse and cultured for 7-10 days to establish a tumor model (the tumor-bearing mice will be used for subsequent in vivo experiments, and all animal experiments performed followed the protocols approved by the Institute of Animal Protection, Chinese Academy of Sciences).

[0145] The successfully constructed 4T1 tumor-bearing mice were divided into two groups (n=3): Example 1 group and Comparative Example 1 group. After both groups of mice were deeply anesthetized by intraperitoneal injection of 100 μL of 29% urethane solution, a blank scan before contrast agent injection was performed, and then Example 1 group (150 μL, gadolinium ion dose of 0.01 mmol / kg, since the contrast agent obtained in Example 1 has an r1 value nearly 20 times that of commercial contrast agents, a lower dose was selected for the experiment) and Comparative Example 1 group (150 μL, gadolinium ion dose of 0.1 mmol / kg) were injected through the tail vein, and then the mice were fixed and placed in a 1.5T micro-magnetic resonance imaging instrument, and T1-weighted imaging was performed at 1h, 2h, 3h, 4h, 5h, and 6h after injection.

[0146] The results are as follows Fig.12 As shown, after two groups of contrast agents were injected into tumor-bearing mice through the tail vein at injection volumes of 0.01mmol / kg and 0.1mmol / kg, respectively, the two groups showed significantly different imaging enhancement effects over time. Among them, the tumor site of Example 1 group had undergone significant changes in 1 hour, and the tumor site reached the brightest at 3 hours, which shows that: the particle size of the contrast agent of Example 1 group can be quickly delivered to the tumor and has a long imaging window; while the dose used in Comparative Example 1 Group (commercial) is 10 times that of Example 1 Group, but it cannot reach the brightness of the contrast agent in Example 1 Group, and because the molecular weight of the contrast agent in Comparative Example 1 Group is relatively small, it is quickly metabolized through the kidneys, and the imaging window is very short, which cannot monitor the lesion site well.

[0147] In summary, the gadolinium-based contrast agent composite material provided by the present invention can effectively improve the longitudinal relaxation rate and the sensitivity of MRI diagnosis, and can also achieve rapid response degradation and release in a short time, thereby extending the imaging window time; and it has good biocompatibility and low toxicity.

[0148] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A gadolinium-based contrast agent composite material with high relaxivity, characterized in that: The gadolinium-based contrast agent composite material comprises a gadolinium-based contrast agent, calcium phosphate and single-molecule micelles; Calcium phosphate is embedded and assembled between adjacent blocks of the unimolecular micelle; The gadolinium-based contrast agent is encapsulated in calcium phosphate; The unimolecular micelle comprises a cyclodextrin-based star-shaped block copolymer; the molecular formula of the cyclodextrin-based star-shaped block copolymer is β-CD-g-[An-b-Bm] 21 , wherein A is the first hydrophilic block, n is the degree of polymerization of the first hydrophilic block, B is the second hydrophilic block, and m is the degree of polymerization of the second hydrophilic block; the first hydrophilic block includes polyacrylic acid; the value of n is 50-60; the second hydrophilic block includes poly(polyethylene glycol methyl ether acrylate) or poly(polyethylene glycol methyl ether methacrylate); the value of m is 8-20; The gadolinium-based contrast agent includes any one of Gd-DO3A, Gd-DOTA or Gd-DTPA; The gadolinium-based contrast agent composite material is prepared by the following preparation method, which comprises: Mixing the single-molecule micelle, the first salt solution and the second salt solution, and performing a hydrothermal reaction to obtain the gadolinium-based contrast agent composite material; The first saline solution comprises the following components: a gadolinium-based contrast agent, a phosphate salt, a sodium salt, and a first buffer; The second salt solution includes the following components: a calcium salt and a second buffer.

2. The gadolinium-based contrast agent composite material according to claim 1, characterized in that: The average particle size of the cyclodextrin-based star-shaped block copolymer is 30-50 nm.

3. The gadolinium-based contrast agent composite material according to claim 1, characterized in that: The preparation method of the cyclodextrin-based star-shaped block copolymer comprises the following steps: (1) mixing a first polymerizable monomer, an initiator, a catalytic composition and a first solvent, and performing a first free radical polymerization reaction to obtain a first polymer precursor; (2) mixing a second polymerizable monomer, a catalytic composition, a second solvent, and the first polymer precursor obtained in step (1), and performing a second free radical polymerization reaction to obtain a cyclodextrin-based star-shaped block copolymer precursor; (3) subjecting the cyclodextrin-based star-shaped block copolymer precursor obtained in step (2) to a hydrolysis reaction to obtain the cyclodextrin-based star-shaped block copolymer.

4. The gadolinium-based contrast agent composite material according to claim 3, characterized in that: The catalytic composition includes a catalyst and a catalyst ligand; The catalyst includes cuprous bromide or cuprous chloride; the catalyst ligand includes pentamethyldiethylenetriamine; Step (1) the first polymerizable monomer includes tert-butyl acrylate; The initiator in step (1) includes 21-Br-β-CD; Step (1) the first solvent comprises methyl ethyl ketone; The molar ratio of the initiator to the first polymerization monomer in step (1) is 1:(500-600); The temperature of the first free radical polymerization reaction in step (1) is 50-70°C; The time of the first free radical polymerization reaction in step (1) is 5-8 hours; Step (2) the second polymerizable monomer comprises polyethylene glycol methyl ether acrylate or polyethylene glycol methyl ether methacrylate; Step (2) the second solvent comprises dioxane; Step (2) the molar ratio of the second polymerizable monomer to the first polymer precursor is 1:(90-110); The temperature of the second free radical polymerization reaction in step (2) is 50-70°C; The time of the second free radical polymerization reaction in step (2) is 22-30 hours; The temperature of the hydrolysis reaction in step (3) is 20-30°C; The hydrolysis reaction time in step (3) is 22-30 hours.

5. The gadolinium-based contrast agent composite material according to claim 1, characterized in that: The mass ratio of the gadolinium-based contrast agent to the unimolecular micelle is 1:(7-12); The average particle size of the gadolinium-based contrast agent composite material is 20-40 nm; The longitudinal relaxation rate of the gadolinium-based contrast agent composite material is > 80 mM -1 s -1 .

6. A method for preparing the gadolinium-based contrast agent composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Mixing the single-molecule micelle, the first salt solution and the second salt solution, and performing a hydrothermal reaction to obtain the gadolinium-based contrast agent composite material; The first saline solution comprises the following components: a gadolinium-based contrast agent, a phosphate salt, a sodium salt, and a first buffer; The second salt solution includes the following components: a calcium salt and a second buffer.

7. The preparation method according to claim 6, characterized in that: The mixing method comprises: mixing the unimolecular micelles and the first salt solution, and then adding the second salt solution thereto; The unimolecular micelle includes a cyclodextrin-based star-shaped block copolymer; The phosphate includes any one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium phosphate, potassium dihydrogen phosphate or dipotassium hydrogen phosphate, or a combination of at least two thereof; The sodium salt includes sodium chloride; The first buffer comprises HEPES saline solution; The molar ratio of the gadolinium-based contrast agent, phosphate and sodium salt is 1:(2-4):(60-80); The mass volume ratio of the gadolinium-based contrast agent and the first buffer solution is 1 mg: (0.8-2) mL; The calcium salt includes any one of calcium chloride, calcium nitrate or calcium acetate, or a combination of at least two thereof; The second buffer comprises a Tris-HCl solution; The molar ratio of the gadolinium-based contrast agent to the calcium salt is 1:(120-130); The mass volume ratio of the calcium salt and the second buffer solution is (25-30) mg:1 mL; The temperature of the hydrothermal reaction is 110-130°C; The hydrothermal reaction time is 20-30min; The hydrothermal reaction was followed by dialysis and freeze-drying.

8. A composition for imaging, characterized in that: The contrast composition comprises a pharmaceutically acceptable adjuvant and the gadolinium-based contrast agent composite material according to any one of claims 1 to 5; The adjuvant includes a diluent.

9. A use of the gadolinium-based contrast agent composite material according to any one of claims 1 to 5, characterized in that: The gadolinium-based contrast agent composite material is used for the preparation of tumor magnetic resonance imaging or detection reagents.

Citation Information

Patent Citations

  • Glucan-gadolinium MRI nanometer developer and preparation method thereof

    CN107899025A

  • Stable cluster-shaped nanometer contrast agent and preparation method and use thereof

    CN109529058A

Cited By

  • Visual perception decision closed-loop nerve regulation and control system

    CN120550342A

  • A visual perception decision closed-loop neuromodulation system

    CN120550342B